Efektivitas Pijat Oksitosin terhadap Pengeluaran ASI pada Ibu Post Partum Normal dan SC: The Effectiveness of Oxytocin Massage on Breast Milk Production in Normal and SC Post Partum Mothers - Kristanti, Yanuar; K, Diah Andriani; Tristanti, Ika (Universitas Ngudi waluyo, 2025)
Breast milk (ASI) contains large amounts of immunity-boosting proteins and fungicides, so exclusive breastfeeding can reduce the risk of infant mortality. Breast milk is produced depending on the hormone prolactin while its release will be assisted by the hormone oxytocin. Oxytocin massage can be a solution in facilitating breast milk, namely by massaging the spine on the ribs 5-6 to the scapula with the hope of being able to induce the parasympathetic nervous system to stimulate the posterior pituitary in the process of producing the hormone oxytocin. The purpose of this study was to determine the effectiveness of oxytocin massage on breast milk production in normal and SC postpartum mothers at Ki Ageng Getas Pendowo Gubug Regional General Hospital. The research method used was a Quasy Experiment two group post test design. The study was conducted at Ki Ageng Getas Pendowo Regional General Hospital in May-June 2025. The independent variable in this study was the provision of oxytocin massage to postpartum mothers and the dependent variable was breast milk production. The population in this study was all mothers who had normal postpartum and SC at Ki Ageng Getas Pendowo Regional General Hospital, totaling 44 respondents. The sampling technique used purposive sampling. Data analysis using univariate and bivariate methods using the Independent T-Test obtained a p-value <0.05, indicating that oxytocin massage is effective in increasing breast milk production in mothers who had normal postpartum and SC. Abstrak Air susu ibu mengandung protein peningkat imunitas dan fungisida dalam jumlah besar, sehingga pemberian ASI eksklusif dapat menurunkan risiko kematian bayi. ASI diproduksi tergantung dari hormon prolaktin semantara untuk mengeluarkannya akan dibantu oleh hormon oksitosin. Pijat oksitosin dapat menjadi solusi dalam memperlancar ASI, yakni dengan memijat bagian tulang punggung pada costa 5-6 hingga scapula dengan harapan mampu menginduksi kerja saraf parasimpatis untuk merangsang hipofise posterior dalam proses produksi hormon oksitosin. Tujuan penelitian ini yaitu untuk mengetahui Efektivitas Pijat Oksitosin Terhadap Pengeluaran ASI Pada Ibu Post Partum Normal dan SC Di RSUD Ki Ageng Getas Pendowo Gubug. Metode penelitian yang digunakan adalah Quasy Eksperiment two group post test design. Penelitian dilakukan di Rumah Sakit Umum Daerah Ki Ageng Getas Pendowo pada bulan Mei-Juni 2025. Variabel bebas dalam penelitian ini adalah pemberian pijat oksitosin pada ibu post partum dan variabel terikatnya adalah pengeluaran ASI. Populasi dalam penelitian ini adalah seluruh ibu post partum normal dan SC di Rumah Sakit Umum Daerah Ki Ageng Getas Pendowo sejumlah 44 responden. Teknik pengambilan sampel dengan cara purposive sampling. Analisa data dengan cara univariat dan bivariat menggunakan uji T-Test Independen, didapatkan hasil nilai p value < 0,05 sehingga pijat oksitosin efektif dalam pengeluaran ASI pada ibu post partum normal dan SC.